The main idea of the whole thesis - Herasymova, Olga (My University, 2016)
The concept of the thesis, topic sentence, or main idea of a piece of writing, the pattern of a typical academic essay is shown in this article. The following assignments will give you practice identifying and extracting the main idea from a body of data.
Keywords: thesis; typical academic essay; article; composition; writer; тези доповідей; типове академічне есе; стаття; твір; письменник; тезисы докладов; типичное академическое эссе; статья; произведение; писатель; кафедра іноземних мов професійного спрямування